IMPLEMENTASI MODEL TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN KEMAMPUAN LITERASI SISWA KELAS V SDN PEDURUNGAN LOR 02 - Miela Desyana; Ikha Listyarini; Monica Ratih Purwaningrum (LPPM Universitas Cipta Mandiri, 2024)
This research aims to analyze the increase in literacy skills of fifth grade students at SDN Pedurungan Lor 02 Semarang before and after using the Teams Games Tournaments (TGT) model. The research design used classroom (PTK) action research which was carried out in class V of SDN Pedurungan Lor 02 Semarang, totaling 26 students, which lasted for 2 cycles. Each cycle consists of two meetings. The dependent variable is students' literacy skills and the independent variable is the Teams Games Tournaments (TGT) model. Data collection methods used include interviews, observation, and documentation with quantitative and qualitative analysis techniques. The research results showed that students' literacy skills after implementing the Teams Games Tournaments (TGT) model in Cycle I obtained a score of 73 and students' completion reached 60%. The increase in critical thinking skills results in cycle II was 82 and the percentage of student completion was 77%. So the application of the Teams Games Tournaments (TGT) model can improve the literacy skills of class V students at SDN Pedurungan Lor 02 Semarang.